Horn's Biologically Active Substances - Can We Replace Horns of Critically Endangered Species (Saiga) by Horns of More Abundant Animals? - Miksík, Ivan; Romanov, Oleg (Natural Products Journal, The, 2017)
The horn of the saiga antelope is often used in Traditional Chinese medicine (TCM). Its “popular” name in Chinese is ‘Lin Yan Jiao’ and the pharmaceutical name is Cornu Antelopis. It is as famous and valuable as musk, pilose antler (Lurong) and rhino horn, the most-renowned medicinal materials of animal origin used in TCM. However, the saiga has also joined the rhinoceros on the list of endangered species. The presented review briefly overviews an existing knowledge regarding the biologically active compounds at saiga horn. The main beneficial effects of the horn, which could be described in scientific terms, are mostly antipyretic and antiulcerative. Despite some indication of its efficacy, no specific compound from the saiga horn has yet been isolated or scientifically described. It can be assumed that the amino acid composition of the horns of various animals: the buffalo, the saiga, the ox and the goat is almost same in terms of nature and composition when they differ only in their ratios. The similarity of amino acid and peptide compounds has confirmed the similarity of anti-inflammatory and antiulcerative physiological actions. Thus, we can talk about the interchanging ability of horns. If someone believes in the positive influence of animal horns on human health, we can thoroughly recommend the use of horns from animals that are more abundant (such as water buffalo, rams) as compared to the critically endangered species such as saiga (or rhinoceros) with possible similar effect on the organism. There are also some evidences that the antipyretic effect is not strictly dependent on the origin of the horn and might be connected to the herbal substances prescribed and used in the preparation of Chinese medicine. However, only some thorough scientific research on TCM could provide new results that can identify the most active components of the extract and confirm our assumptions about the beneficial effects of extracts or powders of the horns.
Keywords: horn